Paleolit Półwyspu Koreańskiego w świetle badań na stanowisku Suyanggae - Bartczak, Marcel (Acta Universitatis Lodziensis. Folia Archaeologica, 2019)
The presented paper is based on my study related with my master’s thesis entitled Palaeolithic of Asia in the light of the international series of the conferences Suyanggae and Her Neighbours. This article focuses on presentation of the results of research concerning one of the biggest Paleolithic site in South Korea. The Suyanggae site is located at Aegok-ri, Jeokseong-myeon, Danyang County, Chungbuk Province, by the South Han River. This site was investigated by Chungbuk National University Museum led by Professor Lee Yung-jo, and the work is still ongoing. It is one of the biggest Palaeolithic site in East Asia. This complex contains over 100.000 lithic artifacts, excavated from three Palaeolithic localities (I, III, VI). The continuity of flint processing is shown in several cultural layers of each locality of Suyanggae complex, started from Lower through Middle to Upper Paleolithic. Moreover, the Suyanggae site shown a large number of lithic assemblages with 50 flint workshops for tool production found in Suyanggae locality I and a few more workshops found in locality VI. The quartz, obsidian, rhyolite and siliceous shale was the main raw material which was utilized to make tools, and the lithic assemblage contains handaxes, cores, blades, flakes, side-scrapers, end-scrapers, tanged points, tanged tools among the others. These findings can confirm this open site to be a huge workshop. In addition, Suyanggae complex probably was used as seasonal camp in warmer periods and the surrounding caves may have been used as shelters when the climate was cooler.